Bibliometric review on factors influencing consumers' intention to purchase electric vehicles - Xinyu Zhu; Hendrik Lamsali (Cogent Business & Management, 2024)
The prevailing global emission pollution dilemma necessitates a sustainable alternative to gasoline-powered automobiles, with electric vehicles serving as a viable option. The shift from petrol to electric cars (EVs) poses a challenge for expanding markets like Malaysia. The Malaysian Automobile Association reported that electric vehicle sales in Malaysia for 2023 totaled 13,257 units. This study examines studies on determinants that affect consumers' intention to acquire electric vehicles. Subsequently, analyzed information regarding the determinants affecting Malaysian customers' propensity to acquire electric vehicles in order to assess prevailing trends. Thirty-six articles published between 2016 and 2023 were extracted from the Scopus databases. The investigation was conducted via bibliometric analysis utilizing VOSviewer software. The subsequent conventional bibliometric indicators employed were: publication year, source type, language, subject area, keyword analysis, geographical distribution, and author citation analysis. Keyword analysis and publication patterns suggest that the determinants affecting consumers' propensity to acquire electric vehicles represent a viable subject for future research.
Keywords: 650; Bibliometric review; electric vehicles; purchase intention; influencing factors; climate change